2001
DOI: 10.1002/dev.1025
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to pacifier experience and feeding in newborn infants

Abstract: This study examined the effects of sucking on a pacifier immediately before feeding on cardiovascular responses to feeding. Twenty-eight bottle-feeding infants were studied at 12 to 40 hr of age. Blood pressure and heart rate measurements were made during three periods: Period 1-while infants rested in their cribs before a regularly scheduled feeding, Period 2-while being held by the feeder immediately before feeding, and Period 3-during the first 3 to 5 min of feeding. Half of the infants were given a pacifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
1
11
0
4
Order By: Relevance
“…Although heart rate is known to increase during infant feeding, 34,35 most studies have relied on bottles or pacifiers to measure NNS as a comparison to NS; on the other hand, we measured heart rate during NS and NNS in breastfeeding infants and found that heart rates were higher during NS compared to NNS, especially during the first month postpartum.…”
Section: Heart Rate and Oxygenationmentioning
confidence: 93%
“…Although heart rate is known to increase during infant feeding, 34,35 most studies have relied on bottles or pacifiers to measure NNS as a comparison to NS; on the other hand, we measured heart rate during NS and NNS in breastfeeding infants and found that heart rates were higher during NS compared to NNS, especially during the first month postpartum.…”
Section: Heart Rate and Oxygenationmentioning
confidence: 93%
“…Lipsitt and co-investigators (44) related their findings in newborns of the associated increase in HR during sucking with liquid (sucrose) compared to sucking with no liquid (non-nutritive) to adaptive gustatory phenomenon; i.e., a slower sucking rate when fed a “savored substance.” Previous studies evaluated HR and HRV in normal, healthy infants during non-nutritive and nutritive sucking with variable results (3, 4, 7, 44, 45). Our results are in line with findings by Cohen et al (3, 4), as well as Portales et al (35), who noted an increase in autonomic function during nutritive feeding from baseline in healthy infants. We noted similar changes in our controls, i.e., increase in HR with nutritive sucking, but with minimal and insignificant change in those with opiate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the ANS status in neonates, investigators have elicited changes in ANS functioning using different stimuli (e.g., nutritive sucking, non-nutritive suck with use of a pacifier, or by tilt or orthostatic changes) (4, 6, 35). Since feeding is a routine activity for newborn infants, we used nutritive sucking to elicit possible changes in ANS functioning and determined measures of HRV in the time domain and the rhythms about the HRV in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento da sucção não-nutritiva possibilita ao recém-nascido uma sucção nutritiva adequada. A sucção não-nutritiva em prematuros estimula o batimento cardíaco (14,15) , propicia adequação da musculatura oral, regulação dos estados de consciência, facilita a digestão, transição para alimentação por via oral mais rápida e fácil, alta hospitalar precoce e maior ganho de peso (16) .…”
Section: Discussionunclassified